Konstruksi Sosial Tradisi Siraman Gong Kyai Pradah di Lodoyo Kabupaten Blitar Jawa Timur - Pratiwi, Diana Yuni; Zuryani, Nazrina; Kamajaya, Gede (Socio-political Communication and Policy Review, 2026)
The Siraman Gong Kyai Pradah tradition in Lodoyo, Blitar Regency, is a sacred cultural heritage that remains preserved and plays a vital role in the social life of the local community. This research aims to analyze how the social construction of the siraman tradition is built, transmitted, and its impacts on the social structure and cultural identity of Lodoyo society. The study employs a descriptive qualitative approach, using observation, in- depth interviews, and documentation as data collection techniques. The main theoretical framework is the social construction theory of Peter L. Berger & Thomas Luckmann (1966), which emphasizes three dialectical processes: externalization, objectivation, and internalization. The findings reveal that the Siraman Gong Kyai Pradah tradition serves not only as a means of social solidarity but also as a mechanism for value transmission, social integration, and the strengthening of community identity. The Siraman Gong Kyai Pradah tradition has undergone objectivation through the symbolism of the gong as a sacred heirloom believed to possess magical and historical powers. This tradition is no longer seen as an ordinary social activity, but has become an objective social reality, recognized and accepted by the community as a cultural heritage. The impact of internalization for the people of Lodoyo is that Siraman Gong Kyai Pradah has become a form of cultural identity. This tradition serves as a spiritual moment not only because of its ritual, but also due to the symbolic meaning that has been internalized from ancestral legends. The impact of externalization is that the community expresses their values and beliefs through the legend of Pangeran Prabu and Mbo Rondo as the sacred origin of the Gong Kyai Pradah. The story of love, loyalty, and betrayal in the tale of Pangeran Prabu and Mbo Rondo reflects the norms and morals of the Lodoyo community.Social negotiation and adaptation processes within this tradition have a direct impact on the economic aspects of the community, particularly for seasonal traders, and provide spiritual influence believed to bring blessings, prosperity, and hope for healing. The study also highlights the importance of adaptation strategies in facing the challenges of preserving tradition amidst modernization. Additionally, the active participation of young generations and support from educational institutions are seen as crucial in maintaining the continuity and meaning of the Siraman Gong Kyai Pradah tradition for the future.